Gastric Volvulus in a 42 Year Old Male: A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Gastric volvulus is a rare clinical entity defined as an abnormal rotation of the stomach around itself beyond physiological range .The diagnosis is made very late as the clinical suspicion is low and mostly diagnosed on imaging or on the surgery table. The purpose of the study to reminding readers of this issue and emphasize the necessity for further research on how to deal with in the best way. Case Presentation: A case of gastric volvulus in a 42 year old male, who presented with abdominal pain, persistent vomiting and retching- a late diagnosis was reached by Barium meal study, after repeated failure to navigate the stomach (Pyloric opening) in consecutive upper GI Endoscopies. Later surgical treatment cured the patient. Conclusion: Although the symptoms like pain and vomiting are common in abdominal diseases and upper GI Endoscopy is a doorstep investigationeven than the diagnosis is made late as the clinical suspicion of gastric volvulus isvery infrequent. To orient the clinician we intend to report this case. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 101-103